Crisis Management System through the Strategy of Diversification of Hotel Enterprise Activities - Sviatoslav KNIAZ; Nellі HEORHIADI; Lubоv LIPYCH; Vitaliy KRUPIN; Оksаnа KHILUKHА; Anatolii SHVORAK; Liudmyla SHOSTAK; Ivanna MАTVIICHUK; Volodymyr YUZEVYCH; Roman ZAYATS; Khrystyna KAYDROVYCH (Communications of International Proceedings, 2021)
The current conditions for carrying out activities in Ukraine require economic entities to form an effective crisis management system. The analysis of the functioning of hotel enterprises showed a decrease in tourist and business activity, a shortage of financing, a low level of service diversification, and seasonal fluctuations in demand. The purpose of the article is to improve the crisis management system based on the strategy of diversification of the hotel enterprise activities taking into account the life cycle stage and the level of crisis management system development which will ensure the elimination of crisis situations. The formation of the crisis management system consists of the following stages: – determination of the life cycle stage based on the calculation of the integral index of the life cycle of the hotel enterprise; – determination of the level of crisis management system development of the hotel enterprise based on the analysis of functional components (anti-crisis planning, anti-crisis organization, anti-crisis motivation, anti-crisis control); – the choice of diversification strategy of the hotel enterprise taking into account the life cycle stage and the level of crisis management system development; – development of measures to improve the crisis management system of a particular hotel enterprise. Improving the crisis management system will ensure the continuity and efficiency of the hotel business.
Keywords: Crisis management system; strategy; diversification of activities; hotel enterprises; life cycle.